THE FERGANA VALLEY AS A SPACE OF CROSS-BORDER POLITICAL INSTABILITY: A GEOPOLITICAL ANALYSIS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The Fergana Valley, a fertile and densely populated region spanning parts of Uzbekistan, Kyrgyzstan, and Tajikistan, has been a persistent hotspot of cross-border political instability in Central Asia. Over the past decade (2015–2025), this valley has witnessed a complex interplay of ethnic tensions, border disputes, and the legacy of arbitrarily drawn frontiers that continue to fuel conflicts. This article provides a geopolitical analysis of the Fergana Valley’s instability, examining the region’s unique specifics, its ethnic mosaic and conflict history. Drawing on scholarly literature and case studies, the article concludes that these dynamics continue to require concerted attention to mitigate the risks of future escalation.